THE PRACTICE OF SUFISM BY THREE ULAMA (AL GHAZALI, AL QUSYAIRI, MUHYIDIN IBNU ‘ARABI) - Putri Arumsari, Ai (Program Studi Ilmu Tasawuf Universitas Pangeran Diponegoro Nganjuk, Jawa Timur, 2026)
This study contains an explanation of the practice of Sufism. This study focuses on three main figures with different approaches to Sufism: Imam Al-Ghazali, Imam Al-Qusyairi, and Muhyiddin Ibn ‘Arabi. Each figure has a unique Sufism practice, based on personal spiritual experiences that are esoteric and difficult to explain rationally. Imam Al-Ghazali emphasized the importance of dhikr, night prayer, and riyadhah for the purification of the soul and the formation of morals, as explained in Ihya' Ulumuddin. Meanwhile, Imam Al- Qusyairi, through his works Risalah al-Qusyairiyyah and Tafsir Al-Qusyairi Lathaif al- Isyarat, prioritized dhikr and jihad an-nafs as the core of his Sufism. Muhyiddin Ibn 'Arabi emphasized intensive dhikr as part of the path of mujahadah, which led to spiritual experiences and a broad understanding of metaphysics. However, limited sources pose a challenge in uncovering the full range of Sufism practices of each figure, particularly Imam Al-Qusyairi and Ibn 'Arabi. Therefore, this study only presents practices that can be verified through authoritative references, to maintain the accuracy and objectivity of the analysis.